Evaluation of Aspects of Continuing Nursing Education Programs in Kirkuk Health Directorate Hospitals (Indian Journal of Forensic Medicine & Toxicology, 2020)
Objective(s): To evaluate the aspects of the Continuing Nursing Education Programs in Kirkuk HealthDirectorate HospitalsMethodology: A descriptive design, using self-evaluation approach, is employed throughout the presentstudy. A non-probability sample of (251) staff nurse are recruited from Kirkuk Health Directorate Hospitals;Kirkuk General Hospital and Azady Hospital. A questionnaire is constructed for the purpose of the studywhich comprised of (1) part, (6) aspects and (52) item. Content validity and internal consistency reliability aredetermined for the questionnaire through a pilot study. Data are collected through the use of the questionnaireand structured interview a means of data collection. Data are analyzed through the application of descriptivestatistical data analysis approach of frequency, percentage, mean of scores, total scores and range.Results: The study indicates that the majority of nurses have evaluated the aspects of the continuing nursingeducation program as poor at Kirkuk Health Directorate.Conclusion: The study concludes that the evaluation of aspects of the continuing nursing education programsis appraised as poor for the majority of nurses’ self-evaluation.Recommendations: The study recommends that mandatory, periodic, systematic and effective evaluation ofcontinuing nursing education program can be carried out for the benefit of both staff nurses, these programsand the quality of nursing care. Further research can be carried out on a large sample size, varied range scaleof variables, large sample size and nation-wide continuing nursing education programs.